SEMANTIC POTENTIAL OF SOUNDS IN COSTUME OF NATIONS OF ANCIENT MIDDLE EAST - Shigurov, Victor; Shigurova, Tatyana (Revista Inclusiones, 2020)
Sounding elements in the costume of the nationalities of the Ancient Middle East are researched in the paper. The urgency of the topic is conditioned by the pendency of the number of problems in the field of genesis and functioning of sounding elements in the costume, as well as by the absence of anintegral, systemic idea about the phenomenon of sounding ornaments,having preserved the semantics of the worldview, ideaofanentity as an integrity being a part of the culture. The objective of the paper consists in definition of the semantic potential of sounding ornaments in the costume of the nationalities of the Ancient Middle East. The sound semantics is considered in close connection with formation of value ideas of society about the surrounding world and the role of a human being in it. The attempt to trace the interconnection of the use of a sound code in the costume is undertaken along with the definition of specific peculiarities of particular culture, characteristic features of the mentality, life attitudes of the representatives of this or that socium. In the study of this problem, the leading approaches are systemic and information-semiotic ones.